2020
DOI: 10.31941/pmjk.v10i2.1247
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Mutu Pelayanan Petugas Kesehatan Terhadap Minat Kunjungan Ulang Pasien Rawat Jalan di Puskesmas X

Abstract: The number of outpatient visits in the X community health center in 2016 was 32633 patients, and in 2017 the number of visits increased by 38374 patients, while in 2018 the number of visits decreased by 36604 patients. Based on data from outpatient visits at X health center that the number of patient visits decreased, where in 2017 increased and in 2018 decreased the number of patient visits. The purpose of the study was to determine the relationship between the quality of health care services and the interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
5

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
1
0
5
Order By: Relevance
“…The existence of good services provided by health workers makes people willing to make repeat visits because they were satisfied. Good service needs to be provided starting from the registration process to carrying out examination actions and the treatment process according to the code of ethics and service standards set (Akbar et al, 2020).The quality of PHCs services need to be continuously improved, especially in aspects that were the main priority, such as the comfort of waiting room, providing disease information and medical action information by health officers clearly, medical services, health officers skill, speed of handling complaints, and employee empathy in giving patients the opportunity submited their complaints, so that later it will have an impact on increasing interest in patient visits for treatment and checking their health again at PHC (Suryani & Arini, 2020). Study at Leyangan Health Center in Semarang District showed that health workers who were less friendly and less concerned about the patient's conditions were able to influence the low community interest in seeking treatment at the PHC (Taekab et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The existence of good services provided by health workers makes people willing to make repeat visits because they were satisfied. Good service needs to be provided starting from the registration process to carrying out examination actions and the treatment process according to the code of ethics and service standards set (Akbar et al, 2020).The quality of PHCs services need to be continuously improved, especially in aspects that were the main priority, such as the comfort of waiting room, providing disease information and medical action information by health officers clearly, medical services, health officers skill, speed of handling complaints, and employee empathy in giving patients the opportunity submited their complaints, so that later it will have an impact on increasing interest in patient visits for treatment and checking their health again at PHC (Suryani & Arini, 2020). Study at Leyangan Health Center in Semarang District showed that health workers who were less friendly and less concerned about the patient's conditions were able to influence the low community interest in seeking treatment at the PHC (Taekab et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Untuk itu setiap petugas diharapkan mampu memperhatikan dan mengontrol emosinya agar tetap stabil, tidak mudah dipengaruhi keadaan atau situasi tertentu, serta dapat menghindarkan perasaan cepat tersinggung atau marah sehingga dapat memberikan pelayanan secara optimal pada setiap pasien yang berkunjung. 28 Sikap positif tenaga kesehatan yang dipersepsikan oleh pasien berdampak pada meningkatnya rasa kepercayaan (trust) yang secara langsung berkontribusi pada loyalitas pelayanan dan meningkatnya niat untuk melakukan kunjungan ulang.…”
Section: Sikap Caring Tenaga Kesehatan Diwujudkan Melaluiunclassified
“…Masyarakat semakin sadar akan kualitas atau mutu pelayanan kesehatan yang mampu memberi kepuasan pada masyarakat itu sendiri. Tujuan pelayanan kesehatan adalah tercapainya derajat kesehatan masyarakat yang memuaskan harapan dan derajat kebutuhan masyarakat (Consumer saticfaction) melalui pelayanan yang efektif oleh pemberi pelayanan yang juga akan memberikan kepuasan dalam harapan dan kebutuhan pemberi pelayanan (Provider satisfaction) dalam institusi pelayanan yang diselenggrakan secara efisien (Institusional satisfaction) (1). Upaya kesehatan tersebut diselenggarakan dengan menitikberatkan kepada pelayanan untuk masyarakat luas guna mencapai derajat kesehatan yang optimal, tanpa mengabaikan mutu pelayanan kepada perorangan (2).…”
Section: Pendahuluanunclassified
“…Kualitas Pelayanan yang tinggi dapat di ciptakan melalui pemenuhan Percieved terhadap variabel Tangibles, Reliability, Assurance, Responsiveness dan Empathy secara optimal sehingga menghasilkan gambaran atau kesan oleh pasien yang baik pada pelayanan kesehatan baik dari segi keramahan petugas, profesionalisme petugas, fasilitas perawat, ketersediaan dan kelengkapan alat penunjang,ketepatan waktu layanan, kesesuaian prosedur penanganan pasien dan ketepatan pengambilan keputusan petugas, (1).…”
Section: Grafik 1 Penilaian Perceived Service Dan Expected Serviceunclassified